Father, Son, and Holy Spirit : essays toward a fully trinitarian theology - Gunton, Colin E. (T & T Clark, 2003)
In this book one of the leading and most popular theologians of our time develops themes he first introduced in 'The Promise of Trinitarian Theology' in 1992, a book which continues to be widely read and used as a textbook in Christian Doctrine throughout the world. Each essay addresses a topic of central importance in Trinitarian theology, ranging from the knowledge of God to the Christian sacraments. Together they reflect in particular on an increasing interest in the doctrine of the Holy Spirit and its bearing on the structure of the doctrine of the Trinity and its various sub-themes of Chri.